Environmental enrichment and serotonergic alterations on depressive-like states in rats - Arndt, David L. (Kansas State University, 2014)
Individuals suffering from depression primarily rely on pharmacological interventions to alleviate the incapacitating symptoms of the disorder. In addition to genetic differences underlying the etiology of depression, environmental factors play a key role as well. For example, environmental enrichment results in various neurotransmitter alterations, significantly affecting serotonin. To test the efficacy of novel antidepressant drugs in the preclinical laboratory setting, researchers commonly implement the forced swim test (FST) for rats or mice. However, the effect of environmental enrichment on the expression of depressive-like states in the FST is unclear, and it is unknown whether environmental enrichment or social isolation can alter the efficacy of the commonly prescribed antidepressant drug, fluoxetine. In the present study, locomotor activity and FST performance were measured after 30 days of rearing in enriched (EC), standard (SC), and isolated (IC) conditions. Results showed that regardless of the significant effect of fluoxetine on locomotor activity in EC, SC, and IC rats, fluoxetine failed to increase swimming and decrease immobility in all three environmental conditions, with enriched-fluoxetine rats displaying significantly less swimming behavior in the FST than enriched rats receiving vehicle control injections. These results suggest that differential rearing, specifically environmental enrichment, can alter the efficacy of antidepressants and may suggest that enrichment reverses the effects of fluoxetine.
Keywords: Environmental enrichment; Fluoxetine; Forced swim test; Locomotor activity; Serotonin; Rats; Behavioral Sciences (0602); Psychobiology (0349); Psychology, Behavioral (0384)